Measuring women’s decisionmaking: Indicator choice and survey design experiments from cash and food transfer evaluations in Ecuador, Uganda, and Yemen - Peterman, Amber; Schwab, Benjamin; Roy, Shalini; Hidrobo, Melissa; Gilligan, Daniel O. (International Food Policy Research Institute, 2015)
Despite wide use of women’s decisionmaking indicators, both as a direct measure of intrahousehold decisionmaking and as a proxy for women’s empowerment or bargaining power, little has been done to explore what such indicators capture and how effective they measure program impacts on empowerment. We review theoretical and operational evidence from recent literature on women’s decisionmaking and analyze survey experiments undertaken in cash and food transfer programs in Ecuador, Yemen, and Uganda from 2010 to 2012. We find large variations in how women are ranked in terms of decisionmaking depending on how indicators are constructed. In addition, we find that across countries, composite decisionmaking indicators are not consistently associated with other proxy measures of women’s empowerment or household welfare, such as women’s education levels or household food consumption. We also find mixed evidence across countries related to the impact of transfer programs on women’s decisionmaking indicators. We conclude with implications of our findings for future research and use of decisionmaking indicators for program evaluation in developing countries.